If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3y = -1 Solving 5x + -3y = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 5x + -3y + 3y = -1 + 3y Combine like terms: -3y + 3y = 0 5x + 0 = -1 + 3y 5x = -1 + 3y Divide each side by '5'. x = -0.2 + 0.6y Simplifying x = -0.2 + 0.6y
| F-63=937 | | a^2+11a+18=1 | | -5n+2n= | | -8-x=x-4r | | 4/31x+8/31=16/31 | | P+1.5=1.5 | | 5(c+4/5)+6=-20 | | 14=7(x-6) | | X/-3+2=9+x | | y=3x-34 | | -1/3(12+9y)=4-3y | | 2/3+1/4t=2 | | y-3=3y-43 | | 7(x-3)+8=2(x-4) | | X/3+2=9+x | | 1-.75x-4x=39 | | 2x=43 | | X+6=.5(12+2x) | | 2(2x-3)=(-1)-x | | 22-83= | | 9n^2-2n-41=0 | | -8x+12=2x+11 | | 2r-6=26 | | 22/2+17= | | 1/2(6-x)+3x=1/2x-8 | | -2x^6-16x^5-32x^4= | | -10=-2x+.33x+5 | | -6+6(3-3v)=102 | | f(x)=4x+6 | | .17y+.07(y+9000)=2790 | | h=a/2 | | 27=4+3(m-8) |